Cassava Peel Extract as Raw Materials for Making Paper : Utilization of Waste as Environmental Conservation - Yogi Kurnia; Durrul Jauhariyah; Madiyo Madiyo; Yoga Nugraha; Muhammad Akhmansyah; Nurhaida Widiani (International Journal of Hydrological and Environmental for Sustainability, 2022)
Today, the continuous use of paper makes various countries experience a tree crisis due to continuous logging. Therefore, the obstacle faced in making paper is the lack of availability of wood raw materials used in the manufacturing process. Currently, various countries are starting to think about other alternatives in paper making. In this study, the use of cassava peels in papermaking can be a solution in meeting the needs of raw materials for papermaking because the content contained in cassava peels can be used as material for making pulp. The experiment of making cassava pulp was carried out using the organosolv process, which is cooking to separate the fibers using organic chemicals. The chemical used in the cooking process is ethanol. The research method used was Completely Randomized Design (CRD). The experiment was carried out with 3 treatments and 3 repetitions. with each concentration of ethanol in the cooking treatment that is 50%, 70% and 90%. Data analysis was carried out by measuring the thickness, gram, age, and tensile strength of the paper. From the experiments conducted, it is proven that using cassava peel can be used as an additional material in making paper. The most effective concentration of ethanol is at a concentration of 90%.